From Codivilla to Ponseti: historical narrative review on clubfoot treatment in Italy - Alberghina, Flavia; Testa, Gianluca; Monforte, Sergio; Pavone, Vito; Andreacchio, Antonio (Annals of translational medicine, 2021)
This narrative review aims to summarize the historical steps of clubfoot treatment in Italy, identifying the centuries-old historical advancement in the deformity management and the most influent involved people. Clubfoot, also referred to as congenital talipes equinovarus, is a relatively common deformity that has significative consequences in the child if it is left untreated. Effective and early treatment of clubfoot has been praised as one of the most successful practice of modern pediatric orthopedics and both surgical and conservative techniques have been proposed over the decades. As an example, Codivilla's posteromedial release (PMR) has been known internationally as one of the milestones of surgical treatment. The narrative review includes clinical studies and reviews concerning clubfoot that were written in English, German and Italian. As an historical review, no limits of years were considered. The search was performed using PubMed, Google Scholar, Scopus, Medline and Cochrane Library databases up to January 2021. A combination of search terms including 'history', 'clubfoot', 'conservative management', 'Codivilla', 'Ponseti method', 'relapse' was utilized. Particular attention was given to papers written by Italian authors. Current clubfoot treatment arises from several studies and clinical research over the centuries. Many surgeons, starting from mid-16th century, have studied the deformity trying to find a successful and effective technique to achieve full correction. Italian scientists, surgeons and prestigious institutions surely took part in this process.